Evaluasi Program Intensif Bahasa Arab pada Kelas Akselerasi di Pondok Pesantren - Mukmin; Hidayah, Nurul; Amelina, Naila (Universitas Islam Ahmad Dahlan Sinjai, 2024)
The Intensive Program in Learning Arabic at MA Raudhatul Ulum is a program that changes the policy of 4 years of study for non-alumni students at MTs Raudhatul Ulum to 3 years like normal Madrasah Aliyah by speeding up the learning process and condensing Arabic language materials intensively. This program has been running since 2008, but there has been no detailed and comprehensive evaluation regarding this program. This research aims to determine the results of an intensive program evaluation in Arabic language learning at MA Raudhatul Ulum using the CIPP model evaluation developed by Daniel L. Stufflebeam, et al. The type of research used is evaluative research with a qualitative approach, data collection using observation, interview and documentation techniques. Meanwhile, analyzing data is carried out by collecting data, reducing data, presenting data, drawing conclusions and verifying data. The results of the CIPP model evaluation in this research show that the intensive program in Arabic language learning at MA Raudhatul Ulum has been implemented well. Of the four components, the Context and Product components are in the very good category, while the other two components, namely Input and Process, are in the good category. Based on these results, it is recommended that the implementation of the intensive program be continued with certain notes.